The Memoirs of Vladas Žukas: Source, Evidence, Reflection - Žukas, Teodoras (Knygotyra, 2025)
The article begins with a personal reflection on the author’s relationship with the bibliographer Vladas Žukas. It then analyzes the memoirs of Vladas Žukas published after 1990. In discussing these publications, the article reconstructs details of the early life of Vladas Žukas by placing particular emphasis on his later daily interactions and his stories about people who were close to him – such as Juozas Balčikonis, Antanas Venclova, Eugenijus Meškauskas, Jonas Dumčius, and others. The article aims to characterize the nature of the ego-documents published by Vladas Žukas, while also assessing them from a source-critical perspective. It argues that his memoirs are a reliable historical testimony revealing the Soviet Lithuanian era in a multilayered way. At the same time, they can be interpreted as a specific case of reflection, illustrating how, at the turn of the 20th and 21st centuries, a personal witness undertook an attempt to remember and interpret the cultural environment of Soviet Lithuania.